2023
DOI: 10.35371/aoem.2023.35.e5
|View full text |Cite
|
Sign up to set email alerts
|

The association of perfluoroalkyl substances (PFAS) exposure and kidney function in Korean adolescents using data from Korean National Environmental Health Survey (KoNEHS) cycle 4 (2018–2020): a cross-sectional study

Abstract: Background Perfluoroalkyl substances (PFAS) are chemicals widely used in various products in everyday life. Due to its unique strong binding force, the half-life of PFAS is very long, so bioaccumulation and toxicity to the human body are long-standing concerns. In particular, effects on kidney function have recently emerged and there are no studies on the effect of PFAS on kidney function through epidemiological investigations in Korea. From 2018 to 2020, the Korean National Environmental Health S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…The implications of our findings are multifaceted, which advances beyond providing awareness and calling for public health intervention to inform future mechanistic research and further understand the complex biological interplay among pollutant mixtures and several chronic and malignant diseases. For instance, the attribution of our findings on metal-and PFAS-induced ROS, which leads to oxidative stress and eventually results in a reduction in kidney function and subsequent damage [81], could be further investigated. This important insight could be useful for the diagnosis of multipollutant-induced chronic disorders and cancers, given the prevalence of multiple pollutants in our environment [84].…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The implications of our findings are multifaceted, which advances beyond providing awareness and calling for public health intervention to inform future mechanistic research and further understand the complex biological interplay among pollutant mixtures and several chronic and malignant diseases. For instance, the attribution of our findings on metal-and PFAS-induced ROS, which leads to oxidative stress and eventually results in a reduction in kidney function and subsequent damage [81], could be further investigated. This important insight could be useful for the diagnosis of multipollutant-induced chronic disorders and cancers, given the prevalence of multiple pollutants in our environment [84].…”
Section: Discussionmentioning
confidence: 97%
“…Pb, Hg, and Cd, which were ranked second, third, and seventh, respectively, on the 2022 priority list of hazardous substances of the Agency for Toxic Substances and Disease Registry [80]. Studies from Yun et al [81] found individual PFAS and their sum (including PFOA and PFOS) to be significantly associated with decreased eGFR (kidney function). The primary toxic effect of these environmental pollutants is the hypertrophic and histological changes they exert on the kidneys as a result of the increased production of reactive oxygen species (ROS), which results in changes in the permeability of microvascular endothelial cells, leading to a reduction in kidney performance [81,82].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their intricate network of nephrons and tubules ensures the efficient removal of waste products, excess fluids, and electrolytes from the bloodstream [17]. Consequently, the exploration of the relationship between PFAS exposure and kidney function has assumed a position of paramount importance in the realm of health research [18]. Extensive research in recent years has shed light on the profound impact of PFAS on kidney health.…”
Section: Of 16mentioning
confidence: 99%
“…Their intricate network of nephrons and tubules ensures the efficient removal of waste products, excess fluids, and electrolytes from the bloodstream [17]. Consequently, the exploration of the relationship between PFAS exposure and kidney function has assumed a position of paramount importance in the realm of health research [18]. Extensive research in recent years has shed light on the profound impact of PFAS on kidney health.…”
Section: Introductionmentioning
confidence: 99%